The correlation between body mass index and menstrual cycle disorders in medical students of Udayana University - Desak Putu Mirah Sawitri; Ari Wibawa; Ni Wayan Tianing; I Dewa Ayu Inten Dwi Primayanti (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2020)
Background: One relevant indicator in describing women's reproductive health and quality of life is the menstrual cycle. A high or low body mass index (BMI) can be a risk factor for menstrual disorders including irregular menstrual cycles, absence of menstruation and menstrual pain. Aim: This study aims to determine the correlation between body mass index and menstrual cycle disorders in medical faculty students of Udayana University. Method: This study used observational analytic study design and cross sectional approach. Samples are selected using purposive sampling technique. The samples were students in Medical Faculty of Udayana University with 90 amount of respondents aged 19-22 years old. Result: Based on chi square statistical test, the results obtained with p value= 0,000 (p value <0,05). Conclusion: The conclusion is there is a significant correlation between body mass index and menstrual cycle disorders in medical faculty students of Udayana University.